Acetylation and Evaluation of Taro Boloso-I Starch as Directly Compressible Excipient in Tablet Formulation - Afewerk Getachew; Zewdu Yilma; Solomon Abrha (Advances in Pharmacological and Pharmaceutical Sciences)
Taro Boloso-I (TB1), a newly improved Colocasia esculenta variety, is a potential source of starch with high yield. However, to improve some limitations of the native starches (NS), such as flowability and compactibility, different physical and chemical starch modifications have been employed. Acetylation is one of the chemical modifications which improves the flow and compaction of the NS, which are prerequisite during direct compression (DC) of tablets. Hence, in this study, TB1 starch was acetylated using acetic anhydride and evaluated as an ideal excipient for direct compression. Starch acetates (SA) with a degree of substitution (DS) of 0.072 (SA1) and 0.695 (SA2) were produced and evaluated. FTIR spectra of the SAs were used to verify the acetylation of the NS. Powder flow evaluation parameters showed significant improvement in the flow properties of the NS following acetylation. In addition, the swelling power, solubility, and compactibility were also improved. Tensile strength (TS) of the tablets comprising SAs only, SA1 (41.40) and SA2 (63.43 Kg/cm2), was significantly higher than tablets made of the NS (31.96) and Starch 1500® (15.12 Kg/cm2). The SAs also showed lower sensitivity towards lubrication than the NS and Starch 1500® as lower lubricant sensitivity ratios were recorded. In addition, tablets comprising the SAs satisfactorily accommodated at least up to 50 % w/w paracetamol—compared to 30 % w/w by Starch 1500®—upon DC processing. The paracetamol tablets comprising SAs also complied with the United States Pharmacopeia specifications for disintegration and dissolution studies. Therefore, taking all the facts into consideration, the SAs could be potential DC excipients in tablet formulations.